Conference Report 3 rd Trialog International Conference “Between Oder and Neman: Issues of Cultural Memory”, Kaliningrad (Russia), 26 th–29th April 2012 - Wawrzyński, Patryk (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761